(untitled) (CIPEEX, 2025)
Footvolley is a sport created in Brazil, with a 50-year tradition, and until now, there was no knowledge about the prevalence of injuries. Thus, the objectives of this study were to analyze the occurrence of injuries, describe the affected anatomical regions, and investigate factors that positively and negatively impact the athletes’ daily lives. A questionnaire was used as a research instrument through Google Forms, applied online via a link sent through the WhatsApp application to 30 amateur athletes aged 16 to 57, who are students at Six Esportes in the city of Ceres-GO. In the data analysis, regarding the frequency of pain after practice or the number of injuries, footvolley predominantly involves the lower limbs. However, for balance and body stability during sports movements, there is intense use of the arms and trunk. For this reason, it was observed that the body region with the highest prevalence of injuries among footvolley athletes is the knee joint, followed by ankle sprains, toe sprains, and back pain. It is noted that a large portion of those diagnosed with injuries after or during the practice of footvolley are long-time practitioners. The predominant use of legs, thighs, and feet in kicks and passes, combined with ground irregularities and daily wear and tear, certainly contributes significantly to the increase in injuries. Regarding injury prevention, it was observed that most respondents report maintaining protective measures such as stretching and specific warm-up exercises before starting training. In line with the responses obtained in this study regarding quality of life and physical well-being, a large part of the athletes seeks to improve physical conditioning, maintain health, lose weight, and evolve in the sport. These observations can be seen as a positive indicator of the practice of footvolley. Therefore, it is concluded that every athlete is subject to injury, whether during training or competition. Proper warm-up and stretching at the beginning of exercise reduce the risk of injuries and, in the end, facilitate increased flexibility and prevent muscle pain.